ACNE Agminata - Report Of 3 Cases - Punia Raj Pal Singh; Kumar Sanjay; Thami Gurvinder P; Mohan Harsh; Nada Ritambhra; Handa Uma (Wolters Kluwer Medknow Publications, 2000)
Acne agminata or lupus miliaris disseminatus faciei is a chronic granulomatous inflammatory disorder-affecting adults of both sexes which terminates spontaneously with scarring. Histopathologically, the papules show granulomas consisting of epithelioif cells, Gaint cells, with or without caseation necrosis along with periappendigeal lymphomononuclear cell infiltrate in the dermis. The exact aetiopathogenesis of this condition is still unknown. We report 3 cases of this uncommon dermatoses recently seen by us.